Microbial Colonization of the Intestinal Epithelium in Suckling Mice - Davis, C. P. (1973)
Colonization by indigenous microorganisms of the mucosal epithelia of the large bowels of suckling mice was followed by microbial culture techniques and by light, fluorescence, and electron microscopy. Certain microbes colonize in distinctive patterns the cecal and colonic epithelia in these mice. Coliforms and enterococci colonize the large bowel 7 to 9 days after birth and reach high population levels during the second week. During that period, these facultative anaerobes can be detected by immunofluorescence techniques in microcolonies in the mucin on the epithelium. During the third week, however, after their populations decline to the low levels characteristic of adult mice, coliforms and enteroccoci can be observed only infrequently in the mucous layer. Anaerobic fusiform-shaped bacteria appear in the mucous layers along with the microcolonies of enterococci and coliforms during the second week after birth. These anaerobes increase in numbers in the mucin until they form thick layers on the mucosal epithelium by the end of the third week. They remain in the mucous layer throughout the life of the normal mouse. Anaerobic spiral-shaped microbes also colonize the mucous layer on the cecal and colonic epithelium. But these organisms can be detected by immunofluorescence in 1-week-old mice, well in advance of the time the fusiform-shaped bacteria can be found. In the second week, the latter microbes co-inhabit the mucous layer with the spiral-shaped organisms. The fusiform- and spiral-shaped microbes remain associated in the mucin on the cecal and colonic mucosal epithelia into the adult life of mice.